Contemporary Swiss Art. - Goerg, Charles (Tel Aviv : Tel Aviv Museum of Art, 1972)
Le Corbusier ; Giacometti, Alberto ; Taeuber-Arp, sophie ; Graeser, Camille ; Lohse, Richard P. ; Bill, Max ; Kemeny, Zoltan ; Oppenheim, Meret ; Rollier, Charles ; Moser, Wilfrid ; Klotz, Lenz ; Raussmüller, Urs ; Müller, Robert ; Tinguely, Jean ; Wiggli, Oscar ; Luginbühl, Bernhard ; Fontana, Annemie ; Vieira, Mary ; Poncet, Antoine ; Staub, Joseph ; Benazzi, Raffael ; Aeppli, Eva ; Presset, Henri ; Hutter, Jean-Albert ; etc.
Contemporary Swiss Art, Tel Aviv Museum, Tel Aviv, November 28, 1972 - January 27, 1973
kunstcatalogus
Keywords: Zwitserland